Genome-wide association study on the body temperature changes of a broiler-type strain Taiwan country chickens under acute heat stress. (May 2019) - Zhuang, Zi-Xuan; Chen, Shuen-Ei; Chen, Chih-Feng; Lin, En-Chung; Huang, San-Yuan
Abstract: Body temperature is the simplest parameter for evaluating the physiological conditions of animals under thermal stress. Genome-wide association studies (GWAS) have identified candidate genes related to economic traits in domestic animals. The present study conducted a GWAS on body temperature changes in a broiler-type strain Taiwan country chickens (TCCs) under acute heat stress. A total of two hundred 30-week-old roosters of a broiler-type strain TCCs were used. The roosters were subjected to acute heat stress at 38 °C for 4 h, and their body temperature was recorded before and during heat stress. The change in body temperature ( ΔT ) of each rooster was calculated according to the difference between the initial temperature and the highest body temperature during heat stress. The roosters were categorized according to survival and ΔT at the end into dead, susceptible, resistant, and intermediate groups. Collected red blood cells were genotyped using a 600 K chicken single-nucleotide polymorphism (SNP) array. A GWAS for ΔT was conducted using the Cochran–Armitage trend test. Significant SNPs were annotated as candidate genes according to the nearest genes. Results indicated that the ΔT of the heat-resistant group was significantly lower than that of the heat-susceptible group. A total of 17 SNPs belonging to 8 candidate genes, 352 SNPs for 78 candidate genes, and 174 significant SNPs for 63 candidate genes were identified in the association analyses in the dead vs. survival, resistant vs. susceptible, and intermediate vs. susceptible groups, respectively. The annotated candidate genes are associated with apoptosis, cellular response to external stimuli, and signal transduction pathways. In conclusion, the significant SNPs located in and proximal to genes in the GWAS analysis were related to apoptosis or responses to external stimuli which serve as potential candidates underlying physiological adaptation to heat stress or thermotolerance in chickens. Highlights: GWAS on body temperature changes in chickens under acute heat stress was performed. Body temperature changes was significantly lower in heat-resistant group. There were 17, 352, and 174 SNPs differed between different thermotolerance groups. The candidate genes mainly associated with apoptosis, response to stimuli, etc.